Analisis Analisis Perubahan Pola Musim dan Distribusi Frekuensi Curah Hujan di Sentani - Pattipeilohy, Wendel Jan; Barung, Femmy Marsitha; Ronsumbre, Ezri Yustina (Stasiun Pemantau Atmosfer Global Lore Lindu Bariri - Palu, 2024)
One important aspect in detecting climate change is by analyzing changes in meteorological variables such as rainfall. This research was conducted to analyze climate change in a simple way in Sentani using rainfall data from the period 1991 – 2020. The method used is qualitative analysis related to the shift in the onset of the rainy season and dry season in period 1 (1991 – 2005) and period 2 (2006 – 2020) compared to their climatological norms. Then, the changes in frequency distribution in each period were compared, and the Mann Whitney statistical test was conducted to test the significance of the average rainfall in each period. Additionally, the Mann Kendall test was used to detect any changes in trends. The results show a shift in the seasonal pattern from the normal, where the onset of the dry season tends to come earlier, and the onset of the rainy season comes later than the normal conditions. There is an increase in rainfall intensity in period 2, where based on the frequency distribution, rainfall in period 1 had a maximum interval of 250 – 300 mm/ten days, while in period 2, the maximum value of the rainfall interval reached 400 – 450 mm/ten days. The Mann Whitney and Mann Kendall statistical tests confirm a significant difference in the average rainfall between the two periods and a significant increase in rainfall over the past 30 years.